Customer perception about innovative safety food delivery during lockdown - SANKAR, DR. JEGANATHAN GOMATHI; MR. NAVEENKUMAR S (The journal of contemporary issues in business and government, 2020)
The research paper titled the customer perception in online food delivery safety during covid. The objective of the study is to identify the factors that influencing customer perception in online food delivery safety to satisfy customer. Descriptive research is used in the study as the research design and the sampling method used is convenience sampling. The sample size of the study is 170 respondents and it is analyzed using spss tool. The collected data were classified, tabulated and analyzed with statistical tools such as frequency analysis and mean analysis. It is found that factor affecting customer perception in online food delivery are delivery problem, preventive and secure,safety service.Among the factors, safety service factor are major influences the customer perception at the time of covid.